Translation and transcultural validation of a quality of life questionnaire to assess facial cosmetics procedures: a Brazilian Portuguese version - Jaqueline Barbeito de Vasconcellos; Daniela Alves Pereira Antelo; Rosane Orofino-Costa (Surgical & Cosmetic Dermatology, 2022)
Background: The increased demand for cosmetic facial treatments is a universal reality, and Brazil is the second country with the most procedures. Quality of life questionnaires can help assess results objectively and reveal data not yet explored in the scientific literature. Thus, the process of translation, adaptation, and validation of questionnaires is necessary for data universalization.